2018
DOI: 10.1007/s10342-018-1154-8
|View full text |Cite
|
Sign up to set email alerts
|

Initial understory response to experimental silvicultural treatments in a temperate oak-dominated forest

Abstract: response to experimental silvicultural treatments in a temperate oak-dominated forest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 64 publications
(95 reference statements)
3
27
1
5
Order By: Relevance
“…With respect to functional traits, CWMs for plant height increased significantly in the disturbed plots, suggesting that taller herbaceous species occupied the newly created canopy gaps, which is in corroboration of the study of [64]. The influx of tall ruderal herbs and grasses in the canopy gaps has been observed before (e.g., [13]).…”
Section: Ecological and Trait-based Perspectivesupporting
confidence: 85%
See 2 more Smart Citations
“…With respect to functional traits, CWMs for plant height increased significantly in the disturbed plots, suggesting that taller herbaceous species occupied the newly created canopy gaps, which is in corroboration of the study of [64]. The influx of tall ruderal herbs and grasses in the canopy gaps has been observed before (e.g., [13]).…”
Section: Ecological and Trait-based Perspectivesupporting
confidence: 85%
“…Forest management determines ecological differences between managed and unmanaged forests that strongly affect plant species diversity and composition [31]. An increase of ground-layer diversity metrics (species richness, cover) along the cutting intensity gradient has been documented in many studies (e.g., [3,63]), and this is usually the result of newly colonized species joining the community and the initial persistence of resident species [64]. A slight increase in tree species richness in canopy gaps suggest that silvicultural objectives were met; canopy gaps created (micro)sites for the establishment of pioneer tree species that were not present in stands under the closed canopy.…”
Section: Floristic Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that retention tree groups in the size of one tree height can mediate the thermal extremes and drying capacity of the ambient air but not their mean values, which are a definite aim in creating aggregated retention trees (Vanha‐Majamaa and Jalonen ). However, we found that minimum T air remains similar in retention tree groups, gap‐cuts, and preparation cuts.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, this trend was also detected for dT soil IQR in the retention tree groups and for maxima in the gap-and preparation cuts. The recovery is presumably based on the natural regeneration of the herb and shrub layer that were considerably different among the treatments (Tinya et al 2019). Before the treatments, understory vegetation was scarce and quasihomogeneous.…”
Section: Temporal Changes Following Forestry Treatmentsmentioning
confidence: 99%